Ion Concentration of Silver Diamine Fluoride Solutions - Iliana Gehui Yan; Faith Miaomiao Zheng; Sherry Shiqian Gao; Duangporn Duangthip; Edward Chin Man Lo; Chun Hung Chu (Elsevier, 2022)
Objective: The aim of this work was to determine the free fluoride and silver ion concentrations and the alkalinity of 4 commercially available 38% silver diamine fluoride (SDF) solutions. Methods: Four common brands of 38% SDF solutions, namely Saforide, Advantage Arrest, e-SDF, and Topamine, were selected. Three bottles of each brand of SDF solution from the same lot were assessed. Measurements of the silver and fluoride content and alkalinity were performed directly when a bottle was opened. Each measurement was repeated to recheck its reliability. The free fluoride ion concentrations were measured using a calibrated ion-selective electrode. The free silver ion concentrations were measured using optical emission spectrometry. The alkalinity of the SDF solution was determined with a pH electrode. Results: The mean concentrations of fluoride ions of the Saforide, Advantage Arrest, e-SDF, and Topamine were 43,233 ppm, 44,333 ppm, 51,370 ppm, and 54,400 ppm, respectively; their percentage differences from the expected value (44,800 ppm) were 3.5%, 2.4%, 14.7%, and 21.4%, respectively. The mean concentrations of silver ions of the Saforide, Advantage Arrest, e-SDF, and Topamine were 258,841 ppm, 260,016 ppm, 336,149 ppm, and 319,966 ppm, respectively; their percentage differences from the expected value (253,900 ppm) were 3.2%, 5.8%, 32.4%, and 25.9%, respectively. The 4 products had pH values of 9.2, 9.1, 9.2, and 9.0, respectively. Conclusions: This study showed differences between the claimed and measured fluoride and silver ion concentrations in 4 common 38% SDF products, which were alkaline with a pH value of 9.